BUSINESS PROCESS ANALYSIS OF CLOUD INCIDENT MANAGEMENT SERVICE WITH ACTIVITY ASSIGNMENT: A CASE OF PT. XYZ (Journal of Business Management and Accounting, 2022)
PT. XYZ is one of the cloud computing service providers in Indonesia. XYZ company started banking and data center software business in 1987, in 2011, the company launched enterprise cloud computing services. This service provides virtual server infrastructure and combines it with network access. The increasing interest of customers who require cloud services allow disruptions to the resources which have been provided. As an experienced company, it has prepared for the disruptions with cloud service management which includes operational aspects of the services. To support the affected services, the company has a Standard Operating Procedure (SOP) which conforms with incident management. However, there are still problems that could potentially interfere with the incident handling process. This can be seen from the observations on the event log where there are indications that activities are not working properly. So, it is necessary to conduct business process analysis to optimize activities of incident management and end-to-end solutions to the customers. The research began with a literature review and data collection. Using the extraction of the event log data and the analysis process, it 806 cases and 5466 activities were found. Then the researchers conducted business process modeling from the event log to run process mining. From the results of process mining and the comparison with the SOP of PT. XYZ, it was found that the business process of incident handling was not implemented. And the average duration of incident handling was 3 to 4 days. This has an impact on the fees charged by PT. XYZ. The result of this research, by processing the data and analyzing the business processes, is knowing the implications for PT. XYZ. Based on the analysis, the researchers provide recommendations that the incident management must increase responsiveness between the service desk and each support team. The optimal incident management development needs to be formed by a functional team for incident monitoring and auto-closed system within a particular time.